Solubility enhancement of biperidine hcl by complexation with hydroxypropyl Î²-cyclodextrin - Dubey, Amit; Singh, Vikram; Juyal, Divya; Rawat, Geeta (Journal of Applied Pharmaceutical Research, 2015)
Oral route is the simplest and easiest way of drug administration, because of the greater stability, lesser bulk, and cheap cost of production, accurate dosage and easy process, solid oral dosage forms have several advantages over other dosage forms. All the poor water soluble drugs after oral administrations are not well absorbed and thus leads to decrease in inherent efficiency of drugs. Therefore, for oral drug delivery system the improvement of drug solubility thereby its oral bio-availability is the most important aspect of drug development process. Biperiden HCl is a potent drug (Maximum daily dose is 16mg/day), having extensive first pass metabolism resulting in poor Bioavailability. The pharmacokinetic profile of this drug showed 33ÃÂ±5 % Bioavailability and 18-24 hours elimination half-life (t1/2). In the present study attempt has been made to prepare and characterize inclusion complex of Biperiden HCl with Hydroxypropyl ÃÂ²-Cyclodextrin. The inclusion complexes prepared by different methods i.e. Physical mixture, Kneading and Solvent evaporation methods. The prepared complexes were characterized using FT-IR. The inclusion complex prepared by Kneading method exhibited greatest enhancing in solubility and faster dissolution (93.98% drug release in 60 min) of Biperiden HCl.